2016
DOI: 10.1074/jbc.m115.712075
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Regulator of G Protein Signaling 8 (RGS8)-Gαq Complex

Abstract: Regulator of G protein signaling (RGS) proteins interact with activated G␣ subunits via their RGS domains and accelerate the hydrolysis of GTP. Although the R4 subfamily of RGS proteins generally accepts both G␣ i/o and G␣ q/11 subunits as substrates, the R7 and R12 subfamilies select against G␣ q/11 . In contrast, only one RGS protein, RGS2, is known to be selective for G␣ q/11 . The molecular basis for this selectivity is not clear. Previously, the crystal structure of RGS2 in complex with G␣ q revealed a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
1
33
1
Order By: Relevance
“…BV-2 cells were treated with LPS (10 ng/ml) for 3 hours, and then cell lysates were immunoprecipitated with Ga i , Ga q , or control antibodies and the associated proteins were immunoblotted for the G proteins and RGS10. Multiple studies have described strong Ga i selectivity of the RGS10 RGS domain (Ajit and Young, 2005;Taylor et al, 2016); however, it has also been reported that RGS10 can display weak interactions with Ga q (Soundararajan et al, 2008). Our results show that LPS activation of BV-2 cells enhances RGS10 association with Ga i , but no detectable association with Ga q was observed ( Fig.…”
Section: Resultssupporting
confidence: 54%
“…BV-2 cells were treated with LPS (10 ng/ml) for 3 hours, and then cell lysates were immunoprecipitated with Ga i , Ga q , or control antibodies and the associated proteins were immunoblotted for the G proteins and RGS10. Multiple studies have described strong Ga i selectivity of the RGS10 RGS domain (Ajit and Young, 2005;Taylor et al, 2016); however, it has also been reported that RGS10 can display weak interactions with Ga q (Soundararajan et al, 2008). Our results show that LPS activation of BV-2 cells enhances RGS10 association with Ga i , but no detectable association with Ga q was observed ( Fig.…”
Section: Resultssupporting
confidence: 54%
“…In animals, RGS proteins typically bind the switch region on their corresponding Gα proteins (60)(61)(62)(63)(64). The reported GAP resistant phosphorylation sites on Gαz were all at N terminus nearby the switch region (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that binding of G␣ q Q209P to RGS proteins might be impaired because they also utilize the SwII as an important contact point. In fact, crystal structures of RGS8 and RGS2 in complex with G␣ q (54,55) have revealed that, despite adopting different poses, both RGS proteins make contact with Gln-209 and several adjacent residues in the SwII (Fig. 5, C and D).…”
Section: Binding Of Rgs Proteins To G␣ Q Q209p Is Weaker Than To G␣ Qmentioning
confidence: 99%